Strategies And Methods of Teaching And Learning Information Technology Terminology (Texas Journal of Multidisciplinary Studies, 2021)
The unprecedented growth of technology and development has made it necessary for contemporary society and its non-expert members to keep up and make use of it. The following article looks into the methods of teaching terminology related to IT